Educational Psychology Intervention in Reducing School Dropout Rates: A Growth Mindset Approach to Marginalized Communities in Indramayu - Fiqih Amrullah; Agus Maksum; Syukron Makmun; Hani Permata Sari; Johadhid Akmal Arif (TA'DIB: Jurnal Pendidikan Agama Islam, 2024)
School dropouts are a complex and multidimensional educational problem, especially in marginalized areas such as Indramayu Regency, West Java. This study aims to examine the effectiveness of growth mindset-based educational psychology interventions in reducing school dropout rates in marginalized communities in Indramayu. Using a descriptive qualitative approach with in-depth interview techniques, participatory observation, and documentation studies, this study involved 30 informants consisting of students who are vulnerable to dropping out of school, parents, teachers, and community leaders. The results of the study showed that growth mindset interventions carried out through Islamic-based counseling guidance programs, teacher training, and community involvement were significantly able to change the mindset of students from a fixed mindset to a growth mindset. This change has an impact on increasing learning motivation, resilience in the face of economic difficulties, and a 23% reduction in school dropout rates in one year of the program. These findings reinforce the urgency of integrating educational psychology approaches in Islamic education policies that favor marginalized communities.